Hechos y palabras : la realidad colombiana vista a través de la prensa escrita (2011)
This paper presents the first application to Colombia of culturomics, a novel research method in the social sciences that describes cultural, social and linguistics trends based on the quantitative analysis of millions of digitized texts. The paper uses all news and editorials published during the past two decades in three national periodicals in order to analyze the trajectories of various phenomena of interest: corruption, economic optimism, the relative power of the judicial branch, etc. Beyond the specific findings, this paper showcases how to use culturomics to describe the changing reality of a developing country.